Developing an Educational Course in Spiritual Care An Action Research Study at Two Danish Hospices - Viftrup, Dorte Toudal; Laursen, Kenneth; Hvidt, Niels Christian 1969- (2021)
Further improvement of spiritual care in palliative care is warranted. Particularly reducing barriers and enhancing spiritual care competencies among the healthcare professionals is needed. The aim was to develop a training course in spiritual care in close collaboration with patients and staff from two Danish hospices. We applied an action research design to ensure that the training course was rooted in everyday practice of patients and staff. The methodology applied was based on philosophical hermeneutics and existential phenomenology. The action research process enabled the division into three topics on how a training course can reduce barriers towards spiritual care among the healthcare professionals. These three topics functioned as a theoretical framework for educating staff at a hospice in spiritual care. The three topics were: (1) the vulnerable encounter; (2) self-reflection concerning spiritual needs, thoughts, beliefs, and values; and (3) shared professional language for spiritual care. We operationalized the three topics into a flexible course design that could be adaptable to the practical possibilities and limitations of the individual hospice. The curriculum includes theoretical teaching, reflection exercises, and an improvisation theater workshop with professional actors. Educating staff led to the improvement of spiritual care at the hospices involved in the study.
Keywords: Denmark; Action Research; Hospice; Palliative Care; Spiritual Care; training course